Cluster-randomized trial of Homework, Organization, and Planning Skills program compared to treatment as usual/waitlist for youth ages 11–14: Study protocol for conceptual replication - Jenelle Nissley-Tsiopinis; Phylicia F. Fleming; Wendy Chan; Joshua M. Langberg; Jaclyn Cacia; Tara Vigil; Brittany Chamberlin; Christina A. Di Bartolo; Katie L. Tremont; Emma H. Walz; Abbas F. Jawad; Jennifer A. Mautone; et al. (PLoS ONE, 2026)
Background Organization, time management, and planning (OTMP) difficulties are associated with academic underachievement. OTMP skills training programs are effective in reducing OTMP deficits and improving academic performance. A randomized controlled trial of Homework, Organization, and Planning Skills (HOPS) for students ages 11–14 found it to be effective with medium to large effects. In that study, HOPS was provided by counselors employed by the research team. This study is a replication examining HOPS under more authentic conditions when providers are employed by schools serving enrolled students. The primary aim is to evaluate HOPS offered by school providers in relation to treatment-as-usual/waitlist (TAU/WL). To respond to limited school resources post-COVID-19, HOPS is also provided by research team members, creating the opportunity to replicate the findings from the prior trial and explore differential effectiveness when HOPS is implemented by school vs. research providers. Methods Students in about 30 schools serving students ages 11–14 will be enrolled. Schools are randomly assigned to HOPS vs. TAU/WL on a 2:1 ratio. Students assigned to HOPS schools are randomly assigned to a school vs. research provider on a 1:1 basis. Providers receive two hours of training and additional assistance on request. Child outcomes related to OTMP skills, homework, and academic performance are assessed at post-treatment, 6-month (from baseline) follow-up, and 12-month follow-up. HOPS sessions are video recorded for fidelity coding. Potential effect modifiers include student ADHD, oppositional defiant, and internalizing symptoms, and family socioeconomic level. Analyses will use mixed effects modeling. The goal of the study is to enroll 135 participants, yielding a minimal detectable effect size of 0.50, within the expected range based on prior research. Discussion The study is unique in examining intervention implementation and effectiveness when intervention is provided under authentic practice conditions. Trial registration This study was registered with clinicaltrials.gov (NCT04465708).